Emission and injection characteristics of corn biodiesel blends in diesel engine. (1st January 2019) - Manigandan, S.; Gunasekar, P.; Devipriya, J.; Nithya, S.
Abstract: In recent years, industries have been investing to develop an alternative fuel to replace the depleting petroleum products which emit higher emission. This paper investigates combustion, performance and emission characteristics of the corn vegetable oil methyl ester with oxygenated additives. Pentanol and titanium oxide are used as additives to increase the efficiency of a diesel engine with reduced emission. A set of experiments are carried out in water cooled multi-cylinder diesel engine at different engine rpm, different engine loads and two different injection pressures. The Diesel, CVOME, CVOME75P20T100, CVOME75P20T200, CVOME75P20T300, CVOME85P10T100, CVOME85P10T200 and CVOME85P10T300 are used as test fuels. The pentanol and titanium oxide nanoparticles are mixed with fuel by ultrasonication process at different ppm. For all testing conditions, biodiesels report the superior results compared to conventional diesel fuel. CVOME75P20 with 5% of titanium dioxide at 300 ppm performs better than other mixture fractions. Results obtained shows that BSFC is improved by 6.3% with CVOME75P20T300 while BP is increased 22% with CVOME75P20T300 compared to diesel at full load condition. Astonishing reductions are seen on CO, HC and smoke emissions with the usage of corn oil biodiesel compared to diesel. Furthermore, 16% reduction in NOx and particulate emission are reported with CVOME75P20T300.